Association of intramammary infection caused by biofilm-producing pathogens with chronic mastitis in dairy cows - S. Boonyayatra (2018)
Biofilm is a self-structure of exopolysaccharide with multiple layers of cells. Biofilm formation is associated with a reduced susceptibility to antibiotics, resulting in chronic infections by pathogens. This study aimed to determine the association between intramammary infection with biofilm-producing bacteria and chronic clinical mastitis in dairy cows. Eighty milk samples from acute and chronic clinical mastitis cases were collected from 52 farms in Chiang Mai and Lamphun provinces in northern Thailand. Forty-eight bacterial isolates were identified from the milk samples. The most prevalent isolated bacteria were streptococci, followed by staphylococci and Escherichia coli. Among these bacterial isolates, only 14 (29.17%) could produce a biofilm, 10 of these isolates were from chronic cases and 4 were from acute cases. There was no statistically significant association between intramammary infection with biofilm-producing bacteria and chronic clinical mastitis. However, biofilm production in vivo and its association with the severity of mastitis should be investigated in future studies. © 2014 Academic Journals Inc.